ATRT-04. LATE DEVELOPMENT OF METACHRONOUS ATYPICAL TERATOID/RHABDOID TUMORS (AT/RTS) OR MALIGNANT RHABDOID TUMOR (MRT) IN THREE PATIENTS WITH GERMLINE SMARCB1 MUTATIONS. Issue 2 (22nd June 2018) - Bendel, Anne; Toledano, Helen; Cohen, Ian; Chi, Susan; Biegel, Jaclyn
Abstract: Atypical teratoid/rhabdoid tumor (AT/RT) and malignant rhabdoid tumor (MRT) are aggressive malignancies that typically occur in children < 3 years of age and historically have a survival of < 30%. Approximately 25% of patients harbor inactivating germline alterations in SMARCB1, which predispose carriers to develop rhabdoid tumors (RTs) between birth to 5 years (median 5 months). Surveillance guidelines for carriers of SMARCB1 (or SMARCA4) alterations recommend screening with brain MRI, abdominal ultrasound and total body MRI up to 5 years of age. We present 3 survivors of AT/RT with germline alterations in SMARCB1 who developed late primary (metachronous) RTs. Case 1 was diagnosed with a posterior fossa (PF) AT/RT at 3.5 years and developed a metachronous temporal lobe AT/RT at 17.8 years. Case 2 was diagnosed with a PF AT/RT and synchronous renal MRT at 2 months and developed a metachronous thalamic AT/RT at 8 years. Case 3 was diagnosed at 9 weeks with a lateral ventricle AT/RT and developed a metachronous disseminated retroperitoneal MRT at 11.5 years. Genetic analyses confirmed the 2 AT/RTs in case 1, the 2 AT/RTs and 1 MRT in case 2, and the 1 AT/RT and 1 MRT in case 3 to be distinct primary tumors. Due to advances in the treatment of AT/RT and MRT, survival rates are improving. The 3 cases presented in this report suggest that tumor surveillance beyond 5 years of age is indicated for patients with germline alterations who are predisposed to cancer.